Degradation of 17β-estradiol by UV/persulfate in different water samples - Yunjie Zhu (IWA Publishing, 2021)
Sulfate radical (•SO4−)-based advanced oxidation processes are widely used for wastewater treatment. This study explored the potential use of UV/persulfate (UV/PS) system for the degradation of 17β-estradiol (E2). The pH of the reaction system can affect the degradation rate of E2 by UV/PS and the optimum pH was 7.0; Br− and Cl− in water can promote the degradation rate, HCO3− has an inhibitory effect on the reaction, SO42− and cations (Na+, Mg2+, K+) have no effect on the degradation rate. The degradation of E2 by UV/PS was a mineralization process, with the mineralization rate reaching 90.97% at 8 h. E2 in the UV/PS system was mainly degraded by hydroxylation, deoxygenation, and hydrogenation. E2 reaction sites were mainly located on benzene rings, mainly carbonylation on quinary rings, and bond breakage between C10 and C5 resulted in the removal of benzene rings and carboxyl at C2 and C3 sites. In the presence of halogen ions, halogenated disinfection by-products were not formed in the degradation process of E2 by UV/PS. E2 in the UV/PS system could inhibit the formation of bromate. The results of this study suggest that UV/PS is a safe and reliable method to degrade E2. HIGHLIGHTS The reaction kinetics, mechanisms and degradation pathways of the UV/PS process in degrading E2 in marine aquaculture water were elucidated.; The fates of E2 in marine aquaculture water were analyzed in the presence of potential interfering factors such as anions (Br−, Cl−, HCO3−, SO42−), cation (Na+, Mg2+, K+) and pH value.; The inorganic disinfection by-products namely bromate of E2 treated by UV/PS was also explored.;